Characterization of phoA, a Bacterial Alkaline Phosphatase for Phi Use Efficiency in Rice Plant - Ram, Babu; Fartyal, Dhirendra; Sheri, Vijay; Varakumar, Panditi; Borphukan, Bhabesh; James, Donald; Yadav, Renu; Bhatt, Arun; Agrawal, Pawan K.; Achary, V. Mohan M.; Reddy, Malireddy K. (Frontiers in Plant Science, 2019)
Fertilizer and herbicide are two major component in the agriculture system for achiving crop productivity. Massive use of orthophosphate fertilizer and herbicides pose threats to reserve phosphate and chance of development of tolerant biotype. Phosphite a phosphate analogue has been proposed beneficial over traditionally using phosphorus fertilizers and herbicides in the agriculture. We developed phoA overexpressing transgenic rice that minimize the popsphate loss and contributes to weed management in the agriculture. The phoA rice lines showed improved root, shoot length and total biomass production under phosphite conditions. Additionally, the complete phenotype and productivity of phoA lines under the phosphite treatment attained similar with that of plants under phosphate sufficient condition. The phytotoxic properties of Phi and the metabolizing properties of the phoA overexpressed lines in the Phi treatment condition relatively control weeds without compromising the transgenic yield. Our results indicated that phoA alone or combination with other phosphite metabolizing gene possibly used an effective ameliorating system for improving crop plant for phi based fertilization and weed management statergy in the agriculture.